Selft-Development Media for Persons with Disabilities in the Digital Age - Azhari; Iqbal Maulana (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2020)
Introduction: This research is a case study that comprehensively analyzes the use of social media as a self-development media with disabilities. Specifically, the benefits of using social media against users with disabilities. In this digital era, it is supposed that digital-based media is used to develop themselves, including those with disabilities. The purpose of this study is to describe the influence of social media use of the self- development of the disabled in Aceh, especially the city of Banda Aceh. Methods: The research is qualitatively based, using in-depth interview methods and Interpersonal communication theory. Results: The results showed that the use of social media has provided greater space and opportunity for people with disabilities to interact and mingle with non-disability persons, increase confidence and optimistic attitude to appear in public as well as in living life, able to seek income, improve the sympathy and awareness of the public to support them, available space and the opportunity to prove self to the community that people with disabilities can also contribute and go public.